Sensitivity analysis of coal mine project investment using fuzzy model - utami, Hasrin citra; Cahyadi, Tedy Agung; Ernawati, Rika (Jurnal Mineral, Energi dan Lingkungan, 2024)
Investment analysis needs to be done to determine the feasibility of a project from an economic perspective. In this research, an investment analysis were applied in a coal mine project. The analysis were considering the results of NPV and IRR. NPV is the result of subtracting discounted costs [8]. IRR is an interest rate that shows the net present value is equal to the total amount of business investment [9]. The methods used in the analysis are the conventional method and the Fuzzy method. Conventional method is done by using NPV and IRR formula in Ms.Excel while Matlab for Fuzzy. The Fuzzy method apply a membership functions, namely triangular fuzzy number. The results of the analysis using conventional methods show an NPV value of $ 14,900,691 or IDR 223 Million with an IRR value of 69.8%. The results of the analysis using the fuzzy method with triangular membership functions showed the NPV values of IDR 232 Million and IRR 40.1 %. From the analysis, it can be seen that the fuzzy method is able to produce a larger NPV but a smaller IRR value whose value is close to conventional methods with the same input variables. So it can be concluded that the fuzzy method is quite well applied in investment analysis and it can help for the final decision of a project